The Influence of Financial Technology and Sharia Compliance on Consumer Trust (A Study on Students of the Faculty of Economics and Business, Mulawarman University, Users of Quick Response Code Indonesian Standard Mobile Banking by Bank Syariah Indonesia) - Putri, Noor Armalia; Purwanti, Purwanti; Fitriah, Rinna Ramadhan Ain; Adawiyah, Rabiatul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This research was conducted by Noor Armalia Putri with the title